3D Modular Construction Made of Precast SFRC-Stiffened Panels - Sannem Ahmed Salim Landry Sawadogo; Tan-Trung Bui; Abdelkrim Bennani; Dhafar Al Galib; Pascal Reynaud; Ali Limam (Infrastructures, 2025)
A new concept of a 3D volumetric module, made up of six plane stiffened self-compacting fiber-reinforced concrete (SFRC) panels, is here studied. Experimental campaigns are carried out on SFRC material and on the thin-slab structures used for this modular concept. The high volume of steel fibers (80 kg/m3) used in the formulation of this concrete allow a positive strain hardening to be obtained in the post-cracking regime observed on the bending characterization tests. The high mechanical material characteristics, obtained both in tension and compression, allow a significant decrease in the module slabs’ thickness. The tests carried out on the 7 cm thick slab demonstrate a high load-bearing capacity and ductility under bending loading; this is also the case for shear loading configuration, although without any shear reinforcements. Numerical simulations of the material mechanical tests were conducted using Abaqus code; the results corroborate the experimental findings. Then, simulations were also conducted at the structural level, mainly to evaluate the behavior and the bearing capacity of the thin 3D module stiffened slabs. Finally, knowing that the concrete module truck transport can be a weak point, the decelerations induced during transportation were characterized and the integrity of the largest 3D module was demonstrated.